Pengaruh Experiental Marketing dan Persepsi Nilai terhadap Loyalitas Konsumen dengan Kepuasan Konsumen Sebagai Variabel Intervening pada Pengunjung Damar Coffee Malang - Adam Fahrudin; M Hufron; Siti Asiyah (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis study aims to determine the effect of experiential marketing and perceived value on consumer loyalty with customer satisfaction as an intervening variable for visitors to damar coffee Malang. The population in this study were all visitors to Damar Coffee Malang City. The sample used is some visitors to Damar Coffee Malang City. The technique used in sampling is accidental sampling technique, the sample selected is 100 respondents. The data were collected using a questionnaire method. The data analysis method used is multiple regression analysis with the help of SPSS software version 14 (Statistical Products and Service Solutions version 14). The results showed that Experiential Marketing has a direct effect on Customer Satisfaction, Perception of Value has a direct effect on Customer Satisfaction, Experiential Marketing has a direct effect on Consumer Loyalty, Perception of Value has a direct effect on Consumer Loyalty, Consumer Satisfaction has a direct effect on Consumer Loyalty, Experimental Marketing has a direct effect on Customer Loyalty. Indirectly on Consumer Loyalty through Customer Satisfaction as an intervening variable and Value Perception indirectly on Customer Loyalty through Customer Satisfaction as an intervening variable.Keywords: Experiential Marketing, Perception of Value, Customer Loyalty and Customer Satisfaction